The influence of the mesoporous TiO2 scaffold on the performance of methyl ammonium lead iodide (MAPI) perovskite solar cells: charge injection, charge recombination and solar cell efficiency relationship. Issue 44 (2nd October 2015) - Matas Adams, Alba; Marin-Beloqui, Jose Manuel; Stoica, Georgiana; Palomares, Emilio
Abstract : This works shows the influence of the mesoporous TiO2 nature over the carrier recombination kinetics and the perovskite efficiency. Abstract : Methyl Ammonium Lead Iodide (MAPI) perovskite solar cells have achieved over 20% light-to-energy conversion efficiency with the use of a thin mesoporous layer of TiO2 as a scaffold for the MAPI. Although other solar cell configurations have also been reported, so far only those containing mesoporous TiO2 (mpTiO2 ) have achieved such performance. Herein we describe an exhaustive study of the effects, on the MAPI solar cell performance, of different synthetic routes to achieve nanocrystalline TiO2 nanoparticles that are used to fabricate the mpTiO2 layer. Furthermore, we also measured the interfacial charge transfer dynamics to elucidate the device function–charge recombination kinetics relationship in the different types of synthesised mpTiO2 . Our results show that the choice of the chemical properties of the mpTiO2 layer is of utmost importance to achieve high solar-to-energy conversion efficiencies with remarkable effects on the measured charge carrier recombination kinetics.